Adverse Drug Events on the Use of Sertraline in Clinical Studies: A Review - Syahrul Hidayat; Irma M. Puspitasari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Major depressive disorder (MDD) and anxiety are known as a widespread public health problem treated with sertraline, a class of Selective Serotonin Reuptake Inhibitor (SSRI) drugs as first-line therapy. However, clinical evidence showed that MDD and anxiety therapy with sertraline has not been optimal due to patient non-compliance associated with adverse drug events (ADE) occurring. A literature search on sertraline clinical study was conducted on the PubMed and Science Direct electronic database in April 2020. A total of 12 articles from 5.664 articles have been selected at the initial screening. A total of 6 articles used sertraline as a testing drug in MDD patients, 2 articles used sertraline as testing drug in anxiety patients, 2 articles with sertraline as a comparative drug, 1 article with sertraline as a positive control, and 1 article with sertraline as an adjuvant in MDD patients. Studies on these articles were carried out worldwide from 2010 to 2019. ADEs that occur due to the use of sertraline were: gastrointestinal disorders, nutritional and metabolic disorders, central nervous system disorders, sweating, sleep disorders, irritability, eye disorders, as well as disorders of the skin and subcutaneous tissues. Nausea is the most common ADE of sertraline. ADEs are affected by several factors such as, age, the sertraline combination therapy, and alcohol consumption.